Implementasi Pemberian Dispensasi Kawin di Pengadilan Negeri Jombang - Andini Permatasari; Lintang Yudhantaka (CV Rewang Rencang, 2025)
The minimum age limit for marriage for both men and women is 19 (nineteen) years. However, under certain conditions, a person who has not met this age limit may apply for dispensation to marry. This study aims to analyze the process of filing an application for dispensation of marriage at the Jombang District Court and the reasons that form the basis for the Judge's decision. Based on PERMA Number 5 of 2019, marriage dispensation is granted by considering the best interests of the child. This study explains the procedure for applying for marriage dispensation at the Jombang District Court, which is carried out in several administrative stages until the trial, with the Judge's determination based on urgent reasons and sufficient evidence.